2017
DOI: 10.3389/fnmol.2017.00138
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Stimulation of Phagocytosis Enhances Amyloid Plaque Clearance; Evidence from a Transgenic Mouse Model of ATTR Neuropathy

Abstract: Hereditary ATTR V30M amyloidosis is a lethal autosomal dominant sensorimotor and autonomic neuropathy caused by deposition of aberrant transthyretin (TTR). Immunohistochemical examination of sural nerve biopsies in patients with amyloidotic neuropathy show co-aggregation of TTR with several proteins; including apolipoprotein E, serum amyloid P and components of the complement cascade. Complement activation and macrophages are increasingly recognized to play a crucial role in amyloidogenesis at the tissue bed l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…The genetic analysis has found that C1q SNPs rs665691, rs158761, rs172378, rs672693, rs9434 and rs294180 correlate with an earlier age of disease onset. C1q activates the classical complement pathway ultimately producing the potent C5a anaphylatoxin, which in turn activates phagocytic cells and induces clearance of TTR amyloid deposits [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The genetic analysis has found that C1q SNPs rs665691, rs158761, rs172378, rs672693, rs9434 and rs294180 correlate with an earlier age of disease onset. C1q activates the classical complement pathway ultimately producing the potent C5a anaphylatoxin, which in turn activates phagocytic cells and induces clearance of TTR amyloid deposits [32].…”
Section: Discussionmentioning
confidence: 99%
“…agonists stimulate phagocytosis and reduce amyloid deposits [18,32]. It is therefore likely the C1q polymorphisms have a causative association with age of onset.…”
Section: Discussionmentioning
confidence: 99%
“…For example, macrophages in the sural nerve of AL patients are activated by amyloid and phagocytose and degrade amyloid protein aggregates and fibrils [ 73 ]. Similarly, macrophages are engaged in removal of TTR deposits in FAP patients [ 240 ] and FAP mouse models [ 265 , 266 , 267 ]. Macrophages also phagocytose β2M amyloid fibrils.…”
Section: Mechanisms Linking Amyloid and Peripheral Neuropathymentioning
confidence: 99%
“…Interfering with the normal function of secretases and suboptimal timing of Aβ peptide removal have been put forward as possible explanations. Timely activation of the innate immune mechanisms, as has been previously been shown in animal model of ATTRMet30 neuropathy, and presently with 5XFAD mouse model of AD offers an alternative therapeutic avenue[33].…”
Section: Discussionmentioning
confidence: 99%